2016
DOI: 10.1111/tpj.13262
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, genetic and evolutionary analysis of a paracentric inversion in Arabidopsis thaliana

Abstract: SummaryChromosomal inversions can provide windows onto the cytogenetic, molecular, evolutionary and demographic histories of a species. Here we investigate a paracentric 1.17‐Mb inversion on chromosome 4 of Arabidopsis thaliana with nucleotide precision of its borders. The inversion is created by Vandal transposon activity, splitting an F‐box and relocating a pericentric heterochromatin segment in juxtaposition with euchromatin without affecting the epigenetic landscape. Examination of the RegMap panel and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 92 publications
(121 reference statements)
2
91
0
Order By: Relevance
“…For example, the inhibitory effect of structural polymorphism is evident within the ∼1.17-Mb heterochromatic knob inversion on Chromosome 4, which is suppressed for crossovers in both wild-type and cmt3 populations ( Fig. 2D; Fransz et al 2000Fransz et al , 2016. Following DSB formation, resection occurs to generate 3 ′ single-stranded DNA that can perform strand invasion of homologous chromosomes (Keeney and Neale 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inhibitory effect of structural polymorphism is evident within the ∼1.17-Mb heterochromatic knob inversion on Chromosome 4, which is suppressed for crossovers in both wild-type and cmt3 populations ( Fig. 2D; Fransz et al 2000Fransz et al , 2016. Following DSB formation, resection occurs to generate 3 ′ single-stranded DNA that can perform strand invasion of homologous chromosomes (Keeney and Neale 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in oil palm DNA hypomethylation of an intronic LINE retrotransposon during tissue culture leads to palm mantling and associated drastic yield reduction [62]. Transposition events can also lead to structural rearrangements including inversions and segmental duplications which can have phenotypic effects [63,64]. The advent of economical long-read sequencing technology will make complete genomic assemblies, and the full assessment of structural differences, a reality, even in crops with large TE complements and genome sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up study showed that the nonrelicts originated recently near the Balkans and spread along the eastÀwest axis of Eurasia, wiping out continental-wide relict populations while incorporating locally adaptive alleles from these (Franc ßois et al, 2008;Lee et al, 2017). For the New World, the North American population arrived at around AD 1600 (Exposito-Alonso et al, 2018a), and most of these probably came from the region near southeastern England and northwestern Germany, carrying an inversion in chromosome 4 (Fransz et al, 2016). Durvasula et al (2017) investigated African A. thaliana and suggested an 'out-of-Africa' demographic model, given the highest genomic variation and numbers of private alleles observed in African accessions.…”
Section: Introductionmentioning
confidence: 99%